Description of a new subgenus Neophylidorea (Diptera: Tipulidae) and a new species - Petersen, Jessica D.; Petersen, Matthew J.; Courtney, Gregory W. (Zootaxa, 2012)
A group of 15 species from the genus Euphylidorea (Alexander, 1972) is identified based on distinct morphology and described as the new subgenus Neophylidorea. Characters of the aedeagus and male genitalia in general allow for unequivocal recognition of this subgenus. Comparisons among other species-groups within Euphylidorea and Neophylidorea subgen. n. Petersen are made. A new species, Neophylidorea vannimwegeni Petersen is described based on two male specimens collected in Michigan, USA. This species can be distinguished by the unique structure of the ventral parameres in the male hypopygium.